Österreichische und deutsche Patientenverfügung aus übersetzungswissenschaftlicher Sicht - Łomzik, Magdalena (Comparative Legilinguistics, 2025)
Living will be the will of patients with regards to their medical treatment in the event they are unable to communicate the will themselves, e.g. due to loss of consciousness. This type of declaration of will is regulated by law in German-speaking countries, while in Poland there is still no clear legal basis for respecting it. Living wills are the subject of numerous discussions led by physicians, lawyers and bioethicists, as well as of theses on that matter. However, due to legal and cultural differences between Poland and German-speaking countries in this area, they can also be a very interesting subject for linguistic research. In this article, the living wills are subjected to Christiane Nord's translation-oriented text analysis in order to draw attention to their characteristics, which may influence the translators' decisions when translating them into Polish.